Manajemen Konflik dalam Organisasi Pendidikan: Tinjauan Sistematis atas Strategi Penyelesaian dan Implikasi terhadap Produktivitas - Dania Fahira Falhi; Dina Talitha Salsabila; Rizka Yulia Mahmud; Moh. Ilham Ali; Mu’alimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Conflict is an inevitable phenomenon in organizational dynamics, whether in the education sector, social sector, or wider society. Conflicts that are not managed properly can lead to disintegration, but if handled appropriately, they can become a means of learning and innovation. This literature review aims to identify sources of conflict, resolution strategies used, and their impact on organizational performance. The research questions asked are: (1) What are the main factors causing conflict in educational and social organizations? (2) What are the most effective conflict resolution strategies according to the context? This research method uses a literature review approach by searching articles through Google Scholar and Publish or Perish (PoP) using the keywords “sources AND levels of conflict.” A total of 20 articles were selected from the period 2021–2025, with a final result of five valid articles that were analyzed thematically. The review results show three main themes: (1) sources of conflict include differences in vision, interests, and resource distribution; (2) conflict resolution strategies vary, ranging from mediation, negotiation, to religious and cultural-based approaches; (3) the impact of conflict is ambivalent, it can decrease performance but also encourage positive change.The conclusion of this study emphasizes the importance of contextual conflict management and opens up opportunities for further research to develop more adaptive resolution models based on local values.